The Effect of Workload, Incentives, and Work Motivation on Nurse’s Performance Mediated by Job Satisfaction - Afrah Afifah Salsabila; Oscar Jayanegara (Dinasti International Journal of Education Management And Social Science, 2025)
This research aimed to analyze the Effect of Workload, Incentives, and Work Motivation on Nurse Performance with Job Satisfaction as a mediating variable. The study employed a quantitative research approach and hypothesis testing. Data was collected using total sampling with a Likert scale (1-5) questionnaire from 165 respondents. The data was analyzed using the Partial Least Squares Structural Equation Model (PLS-SEM). The results indicate that Workload has a negative effect on job satisfaction. Incentives have a positive effect on job satisfaction. Work motivation has a positive effect on job satisfaction. Workload has a negative effect on nurse performance. Incentives have a positive effect on nurse performance. Work motivation has a positive effect on nurse performance. Job Satisfaction has a positive effect on nurse performance. Job satisfaction has a negative effect and mediates the effect of workload on the performance of nurses. Job satisfaction has a positive effect and mediates the effect of incentives on the performance of nurses. Job satisfaction has a positive effect and mediates the effect of work motivation on the performance of nurses.